Migration und religiöse Praxis: Gujarats sunnitische Muslime in den ehemaligen »Homelands« Südafrikas - Koch, Julia (transcript, 2016)
How do Indo-Muslim migrants practice Islam in South Africa? Through the perspective of caste membership, it is also possible to take a look at dynamic Islamic practices.